When Ideologies are Collided: News Article and User Comments Post on Social Media - Parthama, I Gusti Ngurah; Pastika, I Wayan; Netra, I Made; Aryawibawa, I Nyoman (Borong Newinera Publisher, 2025)
The article has an aim to examine the interplay of ideologies in the news text of a social media news post and the corresponding users comment section. The news text promotes a leadership-centered and collectivist ideology. The ideology emphasis unity and public compliance under centralized government direction during the Covid-19 pandemic. Conversely, the users comment section reflects a spectrum of public responses. The comments range from support to critique and alternative ideologies. The data include the news article and its comments beneath the news post were analyzed qualitatively to uncover underlying power dynamics, ideological positions, and sociopolitical implications. The findings reveal that while the news article portrays a cohesive national effort led by the government, the users comment demonstrates significant ideological fragmentation. Meanwhile, supportive comments align with the news text’s collectivist narrative, while user critical comments challenge the government’s authority and effectiveness. This condition reflects counter-ideologies. The analysis highlights the complex negotiation of power and trust in digital discourse. Meanwhile, it competes with ideologies shape in public perceptions and contest dominant narratives. This study underscores the importance of examining online interactions to understand the dynamic relationship between language, power, and ideology in contemporary sociopolitical contexts.